La loyauté d'un laïc: Pierre Elliott Trudeau et le libéralisme canadien - Couture, Claude (L'Harmattan, 1996)
Né à Montréal
Keywords: Libéralisme; Trudeau; Pierre Elliott

Paddling with the Current: Pierre Elliott Trudeau, Étienne Parent, Liberalism, and Nationalism in Canada - Couture, Claude (University of Alberta Press, 1998)
Translators: _:n13984
Keywords: Libéralisme; Nationalisme; Trudeau; Pierre Elliott